Job Satisfaction of Mental Health Workers in Psych?social Rehabilitation Centres in a Rural Area of Greece. - Charalambous, George; Xenikakis, Nikolaos; Skitsou, Alexandra; Biskanaki, Elpiniki; Konstantakopoulou, Olympia (International Journal of Caring Sciences, 2018)
Background: The job satisfaction assessment is of great interest for organizations as it is one of the most reliable feedback factors that can provide meaningful information regarding the workers' evaluation of their working environment. These kind of evaluations can be appropriately used to prevent any underlying problems such as burnout, work-related stress, reduced performance, absence from work, retirements, and internal conflicts directly linked to job satisfaction. Methods: The instrument of data collection derived as a combination of two job satisfaction scales, The Minnesota Questionnaire (MSQ) and the Job Describe Index (JDI). The factor analysis resulted to the formation of five factors; "work development", "work features", "work environment", "relations with colleagues" and "decision-making and initiatives". The Cronbach's alpha for the questionnaire items was 0.85, indicating excellent internal consistency of the questionnaire. A cross-sectional study using convenience sampling was conducted with 87 mental health workers derived from 9 psychosocial rehabilitation centres from the public sector in Chania (Crete, Greece). Statistical analysis included student's t-test, Spearman's correlation coefficient and multivariate linear regression. A two sided p-value of less than 0.05 was considered statistically significant. The Statistical Package for Social Sciences (SPSS) program, version 20.0, was used for the statistical analysis. Results: More than two out of three participants (67.8)% were women, 44.8% of the participants were 36-40 years old, 43.7% were 50-64 years old and the remaining 7.23% of the participants were 22-35 years old. The sample majority (55.2%) were university graduates and only 3.6% were holders of post graduate degrees (MSc/PhD). The highest percentage of the participants were nurses (31%), 29.9% were assistant nurses and 11.5% were social workers. 37.9% had a job description of 20 to 29 years and only 18.4% were new entrants. Low to medium levels of job satisfaction were found, while the work features factor had the highest mean score, andthe relations with colleaguesfactor had the lowest score. Multivariate linear regression analyses' results showed that women had higher mean work development score and work features score than men (p=0.022 and p=0.039, respectively), nurses and/or assistant nurses had lower mean work features score and job satisfaction total score than the other mental health workers (p<0.001 and p=0.002, respectively) and increased educational level was related with decreased work features score and job satisfaction total score (p=0.005 and p=0.011, respectively). Conclusions: The low to medium job satisfaction levels imply the need for radical changes regarding all dimensions related to the working conditions encountered in mental health care facilities in Greece.